(untitled) (Quinto Sol, 2013)
At the end of the 1885 militar campaign, defeated indian populations were left in different conditions of cohesion or internal disintegration, opposing in general a strong resistance against the changes that began to be imposed either as an effect of the expansion of the capitalist relations of production, or due to the imposition of state control mechanisms. Within such context, the principles of “prívate property” and “paternal authority”, being the normative pillars of the legal system, played a determinant role to undermine domestic order. This social organization whose breaking up began with defeat, with deactivation of its military force, could re-adapt somewhat better in those cases in which the political line of natural leadership could survive. Thus, persistance or renewal of leaders, their negotiating capacity (or lack of it), and their compliance or rebellion marked in a categoric way the fate of the indigenous group (parcialidades). The viewpoint of the ethnic leadership constitutes the analytic axis of this paper since we consider it to be decisive to understand the different forms of resistance against the process of material and symbolic expropriation.